2010
DOI: 10.1089/ten.tea.2009.0165
|View full text |Cite
|
Sign up to set email alerts
|

Icariin: A Potential Osteoinductive Compound for Bone Tissue Engineering

Abstract: To effectively treat bone diseases using bone regenerative medicine, there is an urgent need to develop safe and cheap drugs that can potently induce bone formation. Here, we demonstrate the osteogenic effects of icariin, the main active compound of Epimedium pubescens. Icariin induced osteogenic differentiation of preosteoblastic cells. The combination of icariin and a helioxanthin-derived small compound synergistically induced osteogenic differentiation of MC3T3-E1 cells to a similar extent to bone morphogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 28 publications
3
71
0
Order By: Relevance
“…Icariin, extracted from Herba Epimedii, has been proved to play an important role in bone anabolism [22,23,[29][30][31]. Although some of the underlying molecular mechanisms have been partly clarified by previous studies, the relevance of icariin and epigenetic modification remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Icariin, extracted from Herba Epimedii, has been proved to play an important role in bone anabolism [22,23,[29][30][31]. Although some of the underlying molecular mechanisms have been partly clarified by previous studies, the relevance of icariin and epigenetic modification remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Icariin have been proved that is an efficient promoting compound for the anti-osteoporosis, the restoration of bone defects and the bone tissue engineering 11,18,29 . Cartilage has similar embryogenesis with bone, and the promoting of the icariin for the bone regeneration may base on the enhancing of the endochondral ossification 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Icariin could regulate the anabolism of osteoblasts through the up-regulation of BMP-4, BMP-2 and SMAD4 expression 15e17 . In bone tissue engineering, icariin has been proved an efficient accelerator 18,19 . Some reports indicated that the osteoinductive effect of icariin in vivo might be expressed through the process of endochondral ossification 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Icariin is a strong candidate for an osteogenic compound for use in bone tissue engineering (12). A previous study showed that icariin could induce bone marrow stromal cell proliferation (7).…”
Section: Discussionmentioning
confidence: 99%